1997
DOI: 10.1897/1551-5028(1997)016<0283:saopap>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Analysis of Pah and PCB Bioaccumulation Patterns in Sediment-Exposed Chironomus Tentans Larvae

Abstract: Abstract-Larvae of the aquatic insect Chironomus tentans (Insecta: Diptera: Chironomidae) were exposed at the third or fourth instar stage to sediments collected near the outfalls of two aluminum foundries and an aluminum fabrication plant. Biota and sediment bioaccumulation factors (BFs), based on wet tissue weights and dry sediment weights, ranged from 0.07 to 0.27 for polycyclic aromatic hydrocarbons (PAHs) and from 0.22 to 1.42 for polychlorinated biphenyls (PCBs). A higher rate of metabolism of PAHs compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
3
11
1
Order By: Relevance
“…Therefore, relative abundance of individual components of CP mixtures in benthic invertebrates would be expected to be different than those observed in sediment or commercial products. Oliver [22] and Wood et al [23] reported changes in relative abundance of PCBs congeners and polycyclic aromatic hydrocarbons between sediment and benthic invertebrates due to differences in bioavailability and biotransformation rates of individual compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, relative abundance of individual components of CP mixtures in benthic invertebrates would be expected to be different than those observed in sediment or commercial products. Oliver [22] and Wood et al [23] reported changes in relative abundance of PCBs congeners and polycyclic aromatic hydrocarbons between sediment and benthic invertebrates due to differences in bioavailability and biotransformation rates of individual compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical concentrations below the detection limit were assigned a value of zero. Apparently, similarity values tend to plateau at 82% based on numerous previous studies [29], and samples with similarity values ≥; 82% are considered essentially identical.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, by assigning these attributes to the chemicals, the bioaccumulation data are made amenable to ecological similarity and preference analysis. Similarity between the urchin and sediment PCB patterns were quantified by calculating the Bray‐Curtis similarity coefficients [29] for each sediment‐urchin paired data set. The general equation used was where S jk is the percentage similarity of the PCB patterns in the urchins and sediment; X j and X k are the prominence values [ D # F ] for the individual congeners in samples j and k, respectively; D is the concentration of a given congener; and F is the frequency of its occurrence in all samples (number of samples containing the congener/total number of samples).…”
Section: Methodsmentioning
confidence: 99%
“…They are divided into several families, including HSP90, HSP70, HSP60, HSP40, and small HSP (sHSP) according to their molecular size (Mayer, 1997;Santoro, 2000). Stressors, including DOP, that cause oxidative stress also aff ect the expression of HSPs (Wood et al, 1997;Lee et al, 2006). The sHSPs are small stress-induced proteins that function to prevent stress-induced cell damage by binding and maintaining the denatured proteins in a folding-competent state.…”
Section: Small Heat Shock Proteinsmentioning
confidence: 99%